Forecasting sugar sales at the Mosul factory using the Akaike standard - Manahil Abdel Ahad (College of Education for Pure Sciences, 1999)
ABSTRACT: In this paper we display and compare several multivariate models for some multiple time series data. The models all come from the vector autoregressive moving average class so that comparisons between them can easily be made using criteria such as Akaike's information criterion. Which is case study model specification with multivariate time series: vector autoregressive moving average model.